The Political of the Didactics - Szwabowski, Oskar (Hybris, 2017)
In this article I attempt to create and discuss the main connections between politics and teaching. I distinguish four such entanglement: the parties, post-political, critical, and political/post-political. I point out that the studying as the immanent political force is the characteristics of the political/post-political entanglement, while other entanglements are connected with the instrumental relation and with the subjugation of what is educational to what is external.